Interprétation et traduction dans les territoires : hors de la polarité traditionnelle des langues officielles - Nevo, Denise; Fiola, Marco A. (TTR : traduction, terminologie, rédaction, 2002)
Over the past few years, translation and interpretation activity have been on the increase across Canada; the Great North is no exception to this rule. One might ask, however, why translate and interpret into and from aboriginal languages ? The issue of the relevance of aboriginal languages is nowhere more acute than in Nunavut, where the Territorial Government is working towards making Inuktitut the official language of the Government. The road to this ultimate goal is, however, fraught with many challenges. At the other end of the Canadian Arctic, the Yukon First Nations are working on the revitalization of the eight local languages, some on the brink of extinction, in order to bring them up to an equal footing with the two Canadian official languages. In both cases, interpretation and translation are useful firstly, in maintaining the linguistic and cultural diversity of the Territories and, secondly, in enabling the development of those languages with a minority status either from a demographic perspective, or from a social status perspective. This paper describes the current situation in Nunavut and Yukon, two Territories at opposite ends of the Canadian Arctic, taking opposite approaches toward the revitalization of the local languages, and calling for a perspective in opposition with the traditional Canadian official language dichotomy. Depuis quelques années au Canada, les activités de traduction et d’interprétation connaissent une recrudescence considérable, et les langues autochtones du Grand Nord ne font pas exception à la règle. Mais pourquoi traduire et interpréter en langues autochtones ou à partir de celles-ci? Le problème de la pertinence des langues autochtones se pose dans toute son acuité au Nunavut, où le gouvernement territorial souhaite que l’inuktitut devienne la langue de l’administration gouvernementale. Or, les défis à relever avant de parvenir à ce but sont nombreux. À l’autre extrémité de l’Arctique canadien, les Premières nations du Yukon travaillent à la revitalisation des huit ...